2001
DOI: 10.1046/j.1365-2249.2001.01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional T lymphocytes infiltrate implanted polyvinyl alcohol foams during surgical wound closure therapy

Abstract: SUMMARYVacuum-assisted closure involving the implantation of polyvinyl alcohol foam is a technique recently developed for the treatment of patients suffering from either wound infection or chronic wounds. This method has been shown to improve and accelerate wound healing. However, little is known about the cell populations that infiltrate the foam, and their potential role in resolving the infection and promoting granulation tissue formation. Our study demonstrates that wound-implanted foams are mainly infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Research suggests that the combination of a foam interface with negative pressure leads to the application of mechanical microdeformations to wound cells and thereby affects the expression of angiogenic factors 42 . Other essential components of this therapy are the continuous evacuation of wound fluid which leads to the removal of inhibitory angiogenic factors such as matrix metalloproteinases (MMPs) 43, 44 and a modulation of the inflammatory microenvironment of wounds, which finally also controls new vessel formation 44-46 . The foam material interface is critical for the application of micromechanical deformations to wound cells 47 as well as is involved in modulating the migration of inflammatory cells in the treated wounds 46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that the combination of a foam interface with negative pressure leads to the application of mechanical microdeformations to wound cells and thereby affects the expression of angiogenic factors 42 . Other essential components of this therapy are the continuous evacuation of wound fluid which leads to the removal of inhibitory angiogenic factors such as matrix metalloproteinases (MMPs) 43, 44 and a modulation of the inflammatory microenvironment of wounds, which finally also controls new vessel formation 44-46 . The foam material interface is critical for the application of micromechanical deformations to wound cells 47 as well as is involved in modulating the migration of inflammatory cells in the treated wounds 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Other essential components of this therapy are the continuous evacuation of wound fluid which leads to the removal of inhibitory angiogenic factors such as matrix metalloproteinases (MMPs) 43, 44 and a modulation of the inflammatory microenvironment of wounds, which finally also controls new vessel formation 44-46 . The foam material interface is critical for the application of micromechanical deformations to wound cells 47 as well as is involved in modulating the migration of inflammatory cells in the treated wounds 46 . Despite the widespread use of VAC therapy, little is known about the mechanisms of action at the molecular level, and especially about of the mechanisms that regulate neovascularisation in the treated wounds.…”
Section: Introductionmentioning
confidence: 99%
“…This increased infiltration of lymphocyte might have also contributed to the superior healing. The dynamic and distinctive role of lymphocytes in promoting wound healing was demonstrated by other investigators (12,13). It was suggested that the wound cleansing effect of lymphocytes and improved collagen deposition could be the possible effects of lymphocytic infiltration in the wound bed.…”
Section: Discussionmentioning
confidence: 68%
“…Gouttefangeas et al 8 measured the cellular content of the foam from the VAC and found high levels of granulocytes, cd4, cd5 and T cells. They supposed the foam to be an attractive habitat for immune cells, partially recruited by a foreign body reaction.…”
Section: Mechanisms Of Action:-mentioning
confidence: 99%